The relationship between raters' understanding of personality traits and situation dimensions from cues: nothing more than general mental ability? - Parker, Zakiyyah (Organisational Psychology, 2025)
The study of abilities and intelligences in psychology has been an area of interest and debate for over a century. Researchers remain divided as to whether intelligence should be generalised across various domains or should the respective domains be acknowledged and assessed in their individual capacity. This measurement issue is important in the field of industrial/organisational psychology (IOP) as the outcomes of assessments are used to make decisions on recruitment, selection, training, and performance management. More specifically, in the field of rater research, understanding the broad vs. narrow nature of constructs which constitute a good (accurate) judge is a relevant issue. In ongoing research efforts to establish the profile of a good judge, the focus has shifted to understanding the specific abilities that they should possess in addition to general abilities. Specifically, trait induction and situation induction are particularly interesting as these abilities reveal the extent to which judges understand the relationship between traits, situations, and behaviours. The relationship between raters' general mental ability (GMA) and these specific abilities was evaluated. A total of 121 participants completed various ability tests including the International Cognitive Ability Resource (ICAR), Situation Induction Test, and the Short Dispositional Insight Test (S-DIT). The participants also completed the Short Big Five Inventory 2 (BFI-2-S), which assessed their dominant personality traits. A Pearson correlation analysis was conducted to test the hypotheses. Results displayed moderate to large correlations between GMA and specific abilities relevant to understanding traits, situations, and behaviours. Furthermore, a moderate, significant relationship was found between trait induction and situation induction. Finally, there were no significant relationships observed between dispositional reasoning ability and any of the Big Five personality traits. Results of the study contribute to the understanding of the nomological network of rater ability constructs associated with rating accuracy. Practical and theoretical implications were discussed, and suggestions were made for future research.